2015
DOI: 10.1038/boneres.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling controls chondrocyte hypertrophy via indirect regulation of Sox9

Abstract: RBPjk-dependent Notch signaling regulates both the onset of chondrocyte hypertrophy and the progression to terminal chondrocyte maturation during endochondral ossification. It has been suggested that Notch signaling can regulate Sox9 transcription, although how this occurs at the molecular level in chondrocytes and whether this transcriptional regulation mediates Notch control of chondrocyte hypertrophy and cartilage development is unknown or controversial. Here we have provided conclusive genetic evidence lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…S2Dg,Dh). Surprisingly, neither Hes1 LOF or Hes1,5 LOF mutants appeared to exhibit an expanded hypertrophic zone at E18.5, which has been observed previously in several Notch LOF mutant mice and is indicative of a continuous delay in terminal chondrocyte hypertrophy and cartilage matrix catabolism Mead and Yutzey, 2009;Kohn et al, 2012;Kohn et al, 2015). Based on these data, combined with the observation that HEY factor expression increases in maturing and hypertrophic chondrocytes (Fig.…”
Section: Hes1 Overexpression In Mpcs Delays Chondrogenesis and Inducementioning
confidence: 75%
See 3 more Smart Citations
“…S2Dg,Dh). Surprisingly, neither Hes1 LOF or Hes1,5 LOF mutants appeared to exhibit an expanded hypertrophic zone at E18.5, which has been observed previously in several Notch LOF mutant mice and is indicative of a continuous delay in terminal chondrocyte hypertrophy and cartilage matrix catabolism Mead and Yutzey, 2009;Kohn et al, 2012;Kohn et al, 2015). Based on these data, combined with the observation that HEY factor expression increases in maturing and hypertrophic chondrocytes (Fig.…”
Section: Hes1 Overexpression In Mpcs Delays Chondrogenesis and Inducementioning
confidence: 75%
“…Genetic removal of various Notch signaling components ( presenilin1, presenilin2, Notch1, Notch2 and RBPjκ) within MPCs using Prx1Cre or within cartilage progenitor cells using a Col2Cre transgene delays the onset and progression of chondrocyte hypertrophy and cartilage matrix catabolism Kohn et al, 2012), whereas activation of NICD in committed chondrocytes both in vivo and in vitro promotes chondrocyte hypertrophy and cartilage matrix catabolism (Mead and Yutzey, 2009;Kohn et al, 2012). Recently, we have also demonstrated that several of the Notch-mediated effects on cartilage development occur in an RBPjκ-dependent manner (Dong et al, 2010) and are likely to be the consequence of an indirect transcriptional regulation of Sox9 (Kohn et al, 2015). Although the importance of Notch signaling in cartilage development has been well documented, the precise molecular mechanism(s) by which Notch regulates these distinct processes remain unclear or unknown.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Constitutive Notch2 overexpression causes HPCs to spontaneously develop into dedifferentiated HCC cells (79). In addition, Notch-induced malignant hepatocyte transformation is associated with downregulation of hepatocyte-associated genes and Sox9 expression (80). Fate-mapping studies have demonstrated that clear-cell adenocarcinoma (CCA) cells derived from hepatocytes may be converted to a biliary K-19 positive phenotype (81).…”
Section: Role Of Notch In Hcc and Icc Developmentmentioning
confidence: 99%